Pengaruh Destination Image, Memorable Tourist Experience, Dan Green Value Co – Creation Terhadap Revisit Intention Gen Z (Studi Pada Objek Wisata Bukit Skoter Dieng Banjarnegara) - Azzahra, Septiana; Efendi, Bahtiar (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study aims to analyze the influence of destination image, memorable tourist experience, and green value co-creation on tourist’s revisit intention at Skoter Hill, Dieng Banjarnegara. The destination image plays a key role in shaping tourist’s parceptions of a destination, while memorable experiences contribute to their intention to return. Additionally, tourist’s involvement in green value co-creation, which focuses on creating environmentally sustainable practices, is predicted to strengthen revisit intention. The research methodology uses a survey with questionnaires distributed to tourist’s who have previously visited Skoter Hill. The collected data is analyzed using multiple regression analysis to examine the relationships between the variables. The results of this study are expected to provide insights for destination managers in enhancing tourist attraction and loyalty through strengthening destination image, offering memorable tourist experiences, improving accessibility, and involving tourists in creating sustainable values.